The Role of Nursing in Enhancing the Quality of Life for Hemodialysis Patients - Alenezi, Wala Awadh Dahem; Alomran, Ruba Abdulaziz; Alshlagi, Nasser Sanad; Alenezi , Manal Awadh Dahem; Alrashedi , Arwa Abdullah; Alshammari, Reem Wans; Alshammari, Murdhy Fahad; Alenezi, Wedad Awadh Dahem; Al Zahrani, Ahmed Mohammad ahmed; Alzahrani , Mansour juman Ali; aljuwaie , Nahla maan (Journal of Ecohumanism, 2024)
Background: Chronic Kidney Disease (CKD) is a prevalent health issue that requires long-term management, with many patients relying on hemodialysis therapy due to the limited availability of kidney transplants. Hemodialysis patients face significant physical and psychological challenges, which can impact their overall quality of life. Nurses play a crucial role in ensuring patient adherence to hemodialysis regimens and providing high-quality care, yet various factors such as workload, stress, and limited resources may affect their ability to deliver optimal care. Understanding the relationship between the role of nurses and the quality of life in hemodialysis patients is essential for improving treatment outcomes. Methods: This study employed a descriptive quantitative correlation design with a cross-sectional approach. A total of 80 hemodialysis patients were recruited through power analysis. Data collection was conducted using two structured questionnaires: one to assess the quality of life in hemodialysis patients and another to evaluate the role of nurses in providing hemodialysis care. The quality of life questionnaire was adapted from the WHOQOL instrument and used a 4-point Likert scale, with higher scores indicating better quality of life. The nursing role questionnaire assessed key aspects of care, including assessment, planning, implementation, and evaluation. Data analysis was performed using univariate and bivariate statistical methods, with the Spearman rho correlation test used to determine the relationship between nurses’ roles and patients’ quality of life. Results: The study found that 90.8% of nurses demonstrated good performance in delivering hemodialysis care, while 9.2% had lower effectiveness. Regarding patient quality of life, 63.2% of hemodialysis patients reported a high quality of life, while 36.8% had a moderate quality of life. The correlation analysis revealed a significant positive relationship between nurses' roles and patient quality of life (r = 0.520, p = 0.002), indicating that better nursing care is associated with improved patient well-being. Conclusion: The findings highlight the crucial role of nurses in enhancing the quality of life among hemodialysis patients. Effective nursing care, including proper assessment, planning, implementation, and evaluation, contributes to better treatment adherence and overall well-being. Strengthening nurse-patient relationships, reducing nurse fatigue, and providing continuous professional training can further improve the quality of care and patient outcomes. Future research should explore additional interventions to optimize nursing care in hemodialysis settings.